Analisis Transformasi Lahan Menggunakan Citra Satelit Landsat Multi Temporal - Laode Muhamad Irsan; Nur Hasanah; Rahma Musyawarah; Ema Hermawati Garusu; Septianto Aldiansyah (Jurnal Penelitian Pendidikan Geografi, 2024)
Kendari City as a center for industrial, trade, and service activities as well as a provider of urban facilities has become an attraction for residents to move and live, thus having an impact on increasing land transformation. This research aims to assess the capability of remote sensing satellite imagery, especially Landsat 8 Oli Imagery for multi-temporal monitoring of Kendari city land transformation in 2010-2021. The research method used is survey research with the Urban Index (UI). The research results show that the multi-temporal land transformation of the city of Kendari in 2010-2021 using a spectral approach on Citra Landsat shows that the city of Kendari is experiencing an increase in the amount of undeveloped land and conversely, there is a decrease in the amount of undeveloped land. The total area of built-up land in 2010 and 2021 is 6,670 ha and 11,182 ha, respectively. The interpretation results have an accuracy of 85% with a kappa value of 69% (strong). Thus, the results of the interpretation have a strong relationship with the results of checking in the field